The Big Five personality and temperamental traits and its correlation with styles of coping with stress in the fire brigade officers - Justyna Szrajda (Journal of Education Culture and Society, 2017)
Selecting specific professional activities (e.g. a brigade officer) and methods for coping with difficult situations may result from personal predispositions of a given person. Personality is founded on the innate temperament. The way of dealing with stress depends on personality traits whose influence is manifested, amongst other things, in the selection of specific coping styles.